THE LEARNING DEVELOPMENT OF OUTCOME BASED EDUCATION (OBE) DURING THE IMPLEMENTATION OF MBKM CURRICULUM IN THE INFORMATION SYSTEMS STUDY PROGRAM DHYANA PURA UNIVERSITY - Christian Tonyjanto; I Wayan Lasmawan; I Gusti Putu Suharta; Christian Tonyjanto; Aulia Iefan Datya; I Wayan Dharma Suryawan; Ni Nyoman Ayu J. Sastaparamitha (Indonesian Journal of Education (INJOE), 2024)
Curriculum as guidance in education is useful for regulating the process of learning activities. The curriculum in higher education, especially at Undhira, is specifically designed to be able to help initiate and accompany all learning activities that are carried out. This can be seen from the seriousness of the institution to provide superior educational services, indeed it is not easy to design a curriculum. The Information System Study Program in this case develops an output-based curriculum as the way out of the MBKM curriculum and also as a form of responsibility to produce competent graduates. During the development process, the ADDIE method is carried out as one of the methods used, which it helps the study program to see in detail and structure so that the resulting curriculum can be used and goes hand in hand with the institution's plans. In addition to the methods used, the study program also looks at the design of the APTIKOM curriculum so that it is noticeable and relevant with the needs of the industrial world